3D School: Desenvolvendo estratégias Maker para estudantes do ensino técnico integrado do curso eletrotécnica Campus Pesqueira – IFPE - Alcantara, Eurlles Canuto de (2025)
This dissertation investigates the introduction of Maker Culture in the context of integrated technical education in electrotechnics, aiming to transdisciplinarily integrate curricular content and explore the potential of emerging technologies such as 3D printing. The research stems from the observed need to connect the theoretical knowledge studied by students with practical and contemporary applications as a way to increase engagement and promote more meaningful learning. The study is justified by the researcher’s experience at the Federal Institute of Science and Technology of Pernambuco (IFPE), Pesqueira campus, where a possible gap was identified in students’ direct contact with emerging technologies like 3D printing, despite the relevance of these tools to the field of electrotechnics. Additionally, the research addresses the issue of knowledge fragmentation, exploring the concepts of multidisciplinarity, interdisciplinarity, and primarily transdisciplinarity, advocating the latter as an approach capable of integrating different fields of knowledge in the learning process. The central problem of this dissertation lies in how to incorporate Maker Culture transdisciplinarily into the integrated technical electrotechnics course at IFPE, Pesqueira campus. The general objective is to identify ways to implement Maker Culture from this perspective, using emerging technologies. The specific objectives include allowing students to explore creativity and develop soft skills through teamwork, creating 3D-printed objects to assemble a scaled-down micro wind turbine, and finally, developing a didactic sequence that systematizes the process. It is believed that the Maker Culture approach, by stimulating experimentation and the practical application of knowledge, can promote meaningful learning, bridging the gap between theory and real-world applications, and preparing students for the technological challenges of the 21st century. The dissertation also highlights the importance of meaningful learning, based on Ausubel’s theory, as a key element in transforming the educational process. In summary, this research seeks to contribute to the modernization of technical education by proposing an innovative pedagogical approach that values creativity, collaboration, and the practical application of knowledge through the integration of Maker Culture and transdisciplinarity into the electrotechnics course at IFPE Pesqueira. The development of the didactic sequence aims to materialize this proposal, serving as a resource for future implementations and studies in the field.